Lyric Poetry by Women of the Italian Renaissance - Cox, Virginia (Book collections on Project MUSE., 2013)
"Lyric Poetry by Women of the Italian Renaissance is the first modern anthology of verse by Italian women of this period to give a full representation of the richness and diversity of their output. Although familiar authors such as Vittoria Colonna, Gaspara Stampa, and Veronica Gambara are well represented, half of the fifty-four poets featured are unknown even to many specialists. Especially noteworthy is an extensive selection of verse from the period following 1560, which has received little or no critical attention. This later, strikingly experimental, proto-Baroque tradition of verse is reconstructed here for the first time. Virginia Cox creates both a scholarly teaching resource and a collection of poetry accessible to general readers with no previous knowledge of the Italian poetic tradition. Each poem is presented in its original language, accompanied by a translation and commentary. An introduction traces the history of Italian lyric poetry from the fifteenth to the seventeenth century. Cox also provides a guide to meter, rhythm, and rhyme, as well as a glossary of rhetorical terms and a biographical dictionary of authors. Organized thematically, this book offers poems about love, religion, and politics; verse addressed to patrons, friends, family, and places; and polemical and correspondence verse. Four languages are represented: Greek, Latin, literary Tuscan of various levels of standardization, and the stylized rustic dialect of pavan. The volume contains more than 200 poems, of which about a quarter have never before been published in a modern edition and more than a third have not previously been available in English translation."--Publisher description.